2013
DOI: 10.1186/1750-1172-8-81
|View full text |Cite
|
Sign up to set email alerts
|

Behçet’s disease: new insight into the relationship between procoagulant state, endothelial activation/damage and disease activity

Abstract: BackgroundBehçet disease (BD) is associated with a prothrombotic state of unknown origin that may lead to life-threatening events. Calibrated Automated Thrombogram (CAT) and Rotational Thromboelastometry (ROTEM) are two global haemostasis assays that may reveal new insights into the physiopathological mechanisms of the disease and its procoagulant condition.Methods23 BD patients who had no signs or symptoms of current thrombosis and 33 age- and sex-matched controls were included in the study. We performed ROTE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
13
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 56 publications
(57 reference statements)
2
13
0
Order By: Relevance
“…Bilge et al reported a significant increase in maximum clot firmness (MCF) in a cohort of patients with BD, which may indicate a prothrombotic state in this disease. This report is in line with a study we recently published [2] highlighting the usefulness of ROTEM and of the calibrated automated thrombogram for studying the hypercoagulable state in BD patients.…”
supporting
confidence: 91%
“…Bilge et al reported a significant increase in maximum clot firmness (MCF) in a cohort of patients with BD, which may indicate a prothrombotic state in this disease. This report is in line with a study we recently published [2] highlighting the usefulness of ROTEM and of the calibrated automated thrombogram for studying the hypercoagulable state in BD patients.…”
supporting
confidence: 91%
“…Since endothelial dysfunction and vascular involvement in BD play important roles in disease pathogenesis, measurement of parameters related to endothelial function have been proposed for evaluating disease progression in BD patients. Endothelial dysfunction can be assessed by flow-mediated dilatation of the brachial artery by ultrasonography 22 and by measuring high-sensitivity C-reactive protein, 22 homocysteine, 22 ADMA, 22 activated protein C, 41 soluble TM, 41 von Willebrand factor, 41 soluble CD62E (s-CD62E), 42 vascular endothelial growth factor, 43 and endocan levels. 44…”
Section: Evaluation Of Endothelial Dysfunction In Behçet Diseasementioning
confidence: 99%
“…An alteration in the fibrinolytic system is suggested by a correlation between the increase in activity and antigen levels of PAI-1 with disease activity. 42 Increased plasma levels of PAI-1 in patients with BD can be explained by the systemic activation of coagulation which increases thrombin production in response to a stimulus. This induces platelet synthesis, release of active PAI-1, 51,52 and release of TGF β, which therefore may increase PAI-1 synthesis by endothelial cells.…”
Section: Coagulation In Behçet Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…In this study, the changes in coagulation detected by ROTEM showed a tendency to the hypercoagulable state in patients with BD, as demonstrated by accelerated clot formation and increased clot strength. In another study, the ROTEM test showed that elevated levels of fibrinogen and PAI-1 could be associated with the prothrombotic state in patients with BD, and the calibrated automated thrombogram (CAT) assay demonstrated that the plasma obtained from BD patients was capable of generating more thrombin in response to the same stimulus than the plasma drawn from controls [64].…”
Section: Authormentioning
confidence: 99%